Synergetic reorganization of the contralateral structure and function in patients with unilateral frontal glioma - Ge, Honglin; Yan, Zheng; Liu, Dongming; Qi, Wenzhang; Chen, Shanshan; Yang, Kun; Liu, Hongyi; Zou, Yuanjie; Hu, Xinhua; Liu, Yong; Chen, Jiu (Frontiers in Neuroscience, 2022)
Objective This study aimed to investigate the contralateral structural and functional plasticity induced by frontal gliomas. Methods Patients with left (n = 49) or right (n = 52) frontal diffuse glioma were enrolled along with 35 age- matched healthy controls (HCs). The gray-matter volumes (GMVs) of the contralesional region were measured using the voxel-based morphometry (VBM) analysis. Additionally, the amplitude of low-frequency fluctuation (ALFF) of the contralesional region was calculated via resting state functional magnetic resonance imaging (MRI) to assess functional alterations. Result The GMV of the contralateral orbitofrontal cortex of the right or left frontal gliomas was significantly larger than the corresponding GMV in the controls. In the patients with right frontal glioma, the GMV and ALFF in the left inferior frontal gyrus were significantly increased compared with those in the controls. Conclusion Glioma invasion of the frontal lobe can induce contralateral structural compensation and functional compensation, which show synergy in the left inferior frontal gyrus. Our findings explain why patients with unilateral frontal glioma can have functional balance, and offer the possibility of preserving the brain function while maximizing tumor removal.